(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The great powers in Europe have followed a strategy of balance of power, since the sixteenth century, based on alliances or axes, and based on capitalism, which pushed these powers to colonial expansion, especially in the Arab East region, relying on their military superiority. The policy of conspiracies appeared after the Vienna Conference in 1815, which led to a change in the nature of the international balance, and the activity of the policy of the European alliances of the great powers, at the beginning of the twentieth century, and the start of an arms race between them, especially Germany and Britain, which led to the division of Europe into two camps, the first led by Germany and the second Britain, and thus led to the outbreak of the First World War in 1914. The declaration of the Ottoman Empire to stop the war in Germany was the first step, in the eyes of Britain and France, on the path to the birth of the new Middle East, after its policy for a hundred years was to preserve the unity of the Ottoman Empire, This led to the division of the Arab East, and the emergence of four countries, namely Syria, Lebanon, Palestine, Transjordan, and Iraq.